Enhancing PAPR reduction for FBMC-OQAM systems by joint both tone reservation and companding methods - Salima Senhadji; Yassine Mohammed Bendimerad; Fathi Tarik Bendimerad (Institute of Advanced Engineering and Science, 2021)
One of the major problems that faces any wireless communication system that apply multicarrier modulation technology is large Peak-to-Average Power Ratio (PAPR). There are divers PAPR reduction methods to solve this problem. Tone Reservation (TR) scheme is one of the most famous PAPR reduction techniques in which a peak cancelling signal is added to the original one in such a way that PAPR will reduce. Companding is another easy PAPR reduction technique in which compression of large amplitude samples and expansion of low one. In this paper, we suggest a new PAPR reduction scheme based on combining tone reservation and companding techniques for FBMC-OQAM systems. The simulation results show that the new scheme (TR&Compd) presents better result in term of PAPR reduction compared to TR and Companding methods taken separately.